التحصيل المعرفي وعلاقته ببعض المهارات الكشفية لدى مرشدات قسم التربية البدنية وعلوم الرياضة كلية بلاد الرافدين الجامعة - توفيق اعتماد كامل (Journal of Physical Education and Public Health, 2024)
The purpose of this study is to investigate the relationship between cognitive performance and scout skills of girl scouts at the School of Physical Education and Sports Sciences, Mesopotamia University College. A total of 52 students were selected in the 2022/2023 academic year through a strict screening method. Then the research sample was selected by lottery, excluding 4 female mentors in the exploratory experiment and 2 female mentors who were extended. The final research sample was 46 female students, which is a certain proportion (88.46%). Through the results that appeared, the researcher concluded that the research sample individuals were characterized by a (good) level in cognitive achievement by applying the scale to them, in addition to the presence of a significant correlation between cognitive achievement and some Scouting skills for girl guides. Through the conclusions, the researcher recommends the need to pay attention to the cognitive aspect of girl guides and to develop scouting and cognitive abilities as they are the important part of the learning process.